The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11085-008-9099-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete Oxidation of Zinc Powder. Validation of Kinetics Models

Abstract: The kinetics of complete oxidation of different samples of zinc powder by air has been investigated by thermogravimetric measurements under isothermal conditions in the range 973-1,173 K. Particles size was in the 63-80 lm range. We succeeded in carrying out the full oxidation of the powders far above the zinc-metal melting point (692.6 K). This phenomenon is linked to the presence of a thin ZnO layer which confines the liquid metal during the oxidation process. Two kinetics models have been verified. The appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…The oxidation rate decreased with time and it was strongly influenced by temperature. The complete oxidation of indium power at 858 K required more than 100 h whereas the oxidation progress at 1173 K was completed in about 1 h. This behaviour is similar to that found in previous works on the complete oxidation of cobalt [4], zinc [5] and bismuth [6], powders. Moreover, it is observed that the oxidation rate is increased with the diminution of the particle size and therefore the increase of their surface (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The oxidation rate decreased with time and it was strongly influenced by temperature. The complete oxidation of indium power at 858 K required more than 100 h whereas the oxidation progress at 1173 K was completed in about 1 h. This behaviour is similar to that found in previous works on the complete oxidation of cobalt [4], zinc [5] and bismuth [6], powders. Moreover, it is observed that the oxidation rate is increased with the diminution of the particle size and therefore the increase of their surface (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Isothermal experiments conducted with zinc and bismuth show that the kinetic model of the parabolic diffusion of oxygen through an oxide layer can be expressed by the expression [4][5][6]: The validity of the model was checked in the present case without any success. The extra-growth of indium at the surface of the particles observed by SEM show that the kinetic of indium is rather more complex.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Another possibility is a mechanical damage during cooling: smaller particles will lead to thinner scales that are not able to withstand mechanical stresses due to temperature drop during cooling. At this oxidation temperature (950°C), it has not been possible to fit typical oxidation kinetics (pseudoparabolic, asymptotic, logarithmic) or others used for powders at high temperatures [7,8]. This can be related to the polymorphic transformations taken place at this temperature.…”
Section: Fig 2 Weight Gains During 10 H Isothermal Dwellsmentioning
confidence: 99%
“…There are, however, models regarding the thermal oxidation of two metal powders above their melting temperature: zinc [7] and indium [8].…”
Section: Introductionmentioning
confidence: 99%